Geochemical Characteristics of Rare Earth Elements in the Chaluo Hot Springs in Western Sichuan Province, China - Wei, Shuaichao; Liu, Feng; Zhang, Wei; Zhang, Hanxiong; Yuan, Rouxi; Liao, Yuzhong; Yan, Xiaoxue (Frontiers in Earth Science, 2022)
High-temperature hydrothermal activity areas in western Sichuan Province, China are ideal objects for studying deep Earth science, extreme ecological environments, and comprehensive geothermal utilization. To understand the geochemical characteristics of rare earth elements (REEs) in the Chaluo hot springs in western Sichuan Province, the authors analyzed the composition and fractionation of REEs in the hot springs through hydrochemical analysis, REE tests, and North American Shale Composite-normalized REE patterns. Moreover, the composition and complex species of REEs in the geothermal water in the Chaluo area were determined through calculation and simulation analysis using the Visual MINTEQ 3.0 software. The results are as follows. In terms of hydrochemical type, all geothermal water in the Chaluo area is of the Na-HCO3 type. The cations in the geothermal water are mainly controlled by water-rock interactions and evaporation, the anions are determined by water-rock interactions, and the hydrochemical processes are primarily controlled by the dissolution of silicate minerals. The total REE content of the geothermal water in the Chaluo hot springs is 0.306±0.103 ug/L. It is low compared to the Kangding area and is primarily affected by the reductive dissolution of Fe oxides/hydroxides, followed by pH. The geothermal water in the Chaluo area is rich in light rare earth elements (LREEs) because of the presence of Fe oxides. It shows positive Eu and Ce anomalies due to the combined effects of the dissolution of Eh and Mn oxides and surface water. Furthermore, the positive Eu anomalies are also caused by the water-rock interactions between the Qugasi Formation and deep geothermal water. Similar to alkaline water bodies, the complex species of REEs in the geothermal water mainly include Ln(CO3)2-, LnCO3+, and LnOH2+, which is caused by the stability constants of complexation reactions.